Phys’AR as a Learning Innovation: Strengthening Critical Thinking and Argumentation Skills in Applied Physics - Pertiwi, Faninda Novika; Udomsak Kitthawee; Nurul Huda Ramadhan; Izza Aliyatul Muna (Jurnal Pendidikan Fisika, 2025)
Critical thinking and argumentation are essential twenty-first-century skills in physics education. Yet, conventional teaching methods often fail to provide students with sufficient opportunities to practice and develop these abilities. To address this challenge, this study introduced Phys’AR, an Augmented Reality (AR)–based learning medium designed not only to visualize abstract physics concepts but also to embed structured activities for constructing and evaluating arguments. The study employed an explanatory sequential mixed methods design involving 42 undergraduate students of physics education, divided into a 2023 control group and a 2024 experimental group. Quantitative data on critical thinking and argumentation skills were collected through standardized tests and analyzed using normality tests, homogeneity tests, and independent samples t-tests, while qualitative insights were gathered from classroom observations and student interviews. The findings showed that students in the experimental group significantly outperformed those in the control group in critical thinking, with higher post-test averages and more consistent score improvements. Analysis of argumentation revealed that students supported their claims with stronger data when learning with Phys’AR. However, most remained at a medium level in warrants and backings, and rebuttals were generally weak across both groups. These results indicate that Phys’AR is effective in strengthening evidence-based reasoning but requires complementary teaching strategies to promote deeper theoretical justification and counter-argumentation. The novelty of this study lies in extending the role of AR in physics education from a visualization tool to a platform for argumentation and critical reasoning. By highlighting which components of argumentation benefit most from AR and which require additional scaffolding, this research contributes both theoretical and practical insights for advancing critical thinking and argumentation in physics education.